(untitled) (Bioscience Journal, 2023)
Synthetic herbicides have been intensively used in weed control, although often involved in environmental contamination, critically affecting non-target species. However, never was investigated the effect of commercial formulation using atrazine on developing juvenile fish exposed for 35 days. Juveniles (Astyanax altiparanae) (n = 600) were assigned to the following ATZ-exposed groups: 0 (CTR-control), 0.56 (ATZ0.56), 1.00 (ATZ1.00), 1.66 (ATZ1.66) and 11.66 (ATZ11.66) μg/L. We found a 36.6% decrease in juvenile survival rate in the ATZ11.66 group compared to control and other groups. Juveniles from ATZ11.66 also showed hyperglycemia and increased cortisol levels. Increased the imbalance oxidative with an increase in malondialdehyde (MDA) and Carbonylated proteins levels markers in muscle, gills, and liver. We also found increased activity of the antioxidant enzymes superoxide dismutase (SOD) in gills and SOD and catalase (CAT) in muscles from ATZ11.66 fish, and increased glutathione S-transferase (GST) activities in the liver from all exposed groups compared to control. The morphological consequences of this were loss of secondary lamella integrity, increased mucus-secreting cells, hyperplasia, and lamellar fusion, as well as increased aneurysms percentage. The liver showed vascular congestion associated with endothelial hyperplasia, steatosis, and a decrease in the nuclei percentage. Our results showed that exposure to a commercial formulation of ATZ at 11.66 μg/L can be causing an imbalance in the oxidative markers and morphological damages and decreased survival in a juvenile Neotropical species of great ecological relevance and commercial interest.